The female body in Martin Amis’ Money: a satiric portrait - Alkodimi, Khaled Abkar; Omar, Noritah (Universiti Putra Malaysia Press, 2012)
This paper explores Martin Amis’ Money: A Suicide Note (1984) as a satiric portrait of the commodification of the female body in the market place. The paper argues that Amis is not misogynistic or anti-feminist, as many critics claim, but anti-capitalist. He uses means of satire to criticise sexual exploitation of young women in the world of trade. The discussion seeks to identify the satiric devices employed by Amis to showcase how women are rendered ‘interchangeable goods’. It will be shown in this paper that Amis’ primary preoccupation in Money is pornography, as a very profitable industry and as a source of income in contemporary society. Through mockery and satire, Amis illustrates the negative effects of capitalism on the life of the individual and society at large. The discussion concludes with the significance of Amis’ satirical mode of representation, which shows that women are merely victims of a greed-driven business world and society.